Cyclically adjusted budget balances: an alternative approach - Carine Bouthevillain; Philippine Cour-Thimann; Gerrit van de Dool; Pablo Hernández de Cos; Geert Langenus; Matthias Mohr; Sandro Momigliano; Mika Tujula (European Central Bank (ECB), 2001)
Estimates of cyclically-adjusted budget balances, correcting actual government budget balances for business cycle fluctuations, are produced by many institutions, including the European Commission, the IMF and the OECD. This paper presents an alternative approach for the cyclical adjustment of budget balances. The approach is based on a disaggregated method for the calculation of the cyclical component of the budget balance. In this approach, the effects of changes in the structure of demand and national income on government revenue and expenditure are captured. Cases where the various macroeconomic bases are in different phases of the cycle or exhibit fluctuations of different magnitude are taken into account in this way. The computation of the cyclical components of these macroeconomic bases is based on the Hodrick-Prescott filter and takes into account the latest evidence presented in the literature about the properties of this filter. The paper also presents new estimates of the elasticities of individual budget items with respect to the relevant macroeconomic variables. The method is used within the ESCB for the estimation of cyclically adjusted budget balances of the EU countries
Keywords: E32; E60; 330